2022
DOI: 10.1037/cns0000272
|View full text |Cite
|
Sign up to set email alerts
|

Empirical research on fantasy proneness and its correlates 2000–2018: A meta-analysis.

Abstract: We reviewed articles that appeared between 2000 and 2018 and that addressed fantasy proneness as measured by the Creative Experiences Questionnaire (CEQ) or the Inventory of Childhood Memories and Imaginings (ICMI). We searched Google Scholar to identify relevant articles and used the Hunter–Schmidt method to meta-analyze the correlates of fantasy proneness. We identified 132 articles describing 139 samples that together included 24,007 research participants. Effect sizes were large (rs > .50) for hallucinator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 123 publications
(191 reference statements)
1
21
0
1
Order By: Relevance
“…Finally, a proneness to experience auditory hallucinations is a phenomenological property of inner speaking that could relate to creative potential in yet another manner. (Auditory) Hallucination proneness correlates positively with a tendency to have fantasy experiences (Crowe et al, 2011; Merckelbach et al, 2021; Merckelbach & van de Ven, 2001). Fantasy proneness, in turn, positively correlates with self-reported creative ability (Lack et al, 2003; Lynn & Rhue, 1986).…”
Section: Varieties Of Inner Speech and Creative Potentialmentioning
confidence: 99%
“…Finally, a proneness to experience auditory hallucinations is a phenomenological property of inner speaking that could relate to creative potential in yet another manner. (Auditory) Hallucination proneness correlates positively with a tendency to have fantasy experiences (Crowe et al, 2011; Merckelbach et al, 2021; Merckelbach & van de Ven, 2001). Fantasy proneness, in turn, positively correlates with self-reported creative ability (Lack et al, 2003; Lynn & Rhue, 1986).…”
Section: Varieties Of Inner Speech and Creative Potentialmentioning
confidence: 99%
“…A common self-report measure of fantasy proneness is the Creative Experiences Questionnaire (CEQ; . A recent meta-analysis showed that self-reported dissociative symptoms and CEQ scores are strongly correlated (r = 0.52; Merckelbach et al, 2021). Fantasy proneness comes close to the DSM-5 AMPD trait unusual beliefs and experiences, which is described as beliefs of unusual abilities (e.g., mind-reading, telekinesis), thought-action fusion, and unusual (e.g., hallucination-like) experiences of reality (APA, 2013;Krueger et al, 2012).…”
Section: Fantasy Proneness and Cognitive Dysregulationmentioning
confidence: 99%
“…Fantasy-prone individuals tend to be more highly hypnotizable than average and have vivid imaginal experiences, hence this trait may also be relevant to explain RS. A meta-analysis showed that this construct relates moderately to strongly with absorption, dissociation measures (which typically involve items measuring absorption), schizotypy (which is not necessarily pathological, e.g., Holt et al, 2020), and excessive daydreaming, but only weakly with depression and anxiety (Merkelbach et al, 2021). Terms such as "fantasies," "addicted to fantasizing," and "fantasy-prone personalities" have already been used to describe people with FP, whose spectrum ranges from healthy to pathological (Wilson and Barber, 1982).…”
Section: Absorption Dissociation and Fantasy Pronenessmentioning
confidence: 99%
“…Terms such as "fantasies," "addicted to fantasizing," and "fantasy-prone personalities" have already been used to describe people with FP, whose spectrum ranges from healthy to pathological (Wilson and Barber, 1982). Some studies have shown that the presence of FP is connected to the experience of parapsychological phenomena, the presence of paranormal beliefs, and to reports of various anomalous experiences (Bartholomew et al, 1991;Cardeña and Alvarado, 2014;Dasse et al, 2015;Merkelbach et al, 2021).…”
Section: Absorption Dissociation and Fantasy Pronenessmentioning
confidence: 99%